Mercury's magnetopause and bow shock from MESSENGER Magnetometer observations. Issue 5 (28th May 2013) - Winslow, Reka M.; Anderson, Brian J.; Johnson, Catherine L.; Slavin, James A.; Korth, Haje; Purucker, Michael E.; Baker, Daniel N.; Solomon, Sean C.
Abstract: [1] We have established the average shape and location of Mercury's magnetopause and bow shock from orbital observations by the MESSENGER Magnetometer. We fit empirical models to midpoints of boundary crossings and probability density maps of the magnetopause and bow shock positions. The magnetopause was fit by a surface for which the positionR from the planetary dipole varies as [1 + cos( θ )] − α, where θ is the angle betweenR and the dipole‐Sun line, the subsolar standoff distance R ss is 1.45 R M (where R M is Mercury's radius), and the flaring parameter α  = 0.5. The average magnetopause shape and location were determined under a mean solar wind ram pressure P Ram of 14.3 nPa. The best fit bow shock shape established under an average Alfvén Mach number ( M A ) of 6.6 is described by a hyperboloid having R ss  = 1.96 R M and an eccentricity of 1.02. These boundaries move as P Ram and M A vary, but their shapes remain unchanged. The magnetopause R ss varies from 1.55 to 1.35 R M for P Ram in the range of 8.8–21.6 nPa. The bow shock R ss varies from 2.29 to 1.89 R M for M A in the range of 4.12–11.8. The boundaries are well approximated by figures of revolution. Additional quantifiable effects of the interplanetary magnetic field are masked by the large dynamic variability of these boundaries. The magnetotail surface is nearly cylindrical, with a radius of ~2.7 R M at a distance of 3 R M downstream of Mercury. By comparison, Earth's magnetotail flaring continues until a downstream distance of ~10 R ss . Key Points: Observe Mercury's magnetopause and bow shock from 3 Mercury years in orbit. Establish the time‐averaged shape of the magnetopause and bow shock. Assess solar wind and IMF influence on the magnetopause and bow shock.